Analysis Of Political Branding Of The Gerindra Party Through Tiktok Social Media Towards Generation Z In Jakarta: Case Study Of The 2024 Election Campaign - Adisti Rahmadiany; Muhammad Prakoso Aji (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
The presence of social media is now a new space in politics, which allows politicians like Gerindra party to communicate more closely with the public, especially Generation Z who dominate the use of digital platforms. Through TikTok, Gerindra Party seeks to change its old image that is considered rigid with a more modern and attractive branding strategy, while preparing for the 2024 Election where young voters account for 55% - 60% of the total vote. This research wants to identify how Gerindra Party uses social media to build its political branding towards Gen-Z in Jakarta in the 2024 election. This research uses a qualitative method that emphasizes descriptive research and uses analysis. With a theoretical foundation that serves as a conceptual framework to direct research according to field facts. This method allows researchers to obtain accurate findings by using Bruce Newman's political branding theory to produce an in-depth understanding of the context and dynamics of the research studied. This research underscores that social media is an effective tool for modern political campaigns and consistent branding and can increase the trust of youth voters. The results of this study explain that Gerindra Party has successfully built its political branding on TikTok social media. With the popularity gained, Gerindra Party also experienced an increase in electability during the 2024 Election. The uniqueness in the communication style used also received a good response from the public on social media.